Consultation services for social work supervisors at the Department of Social Services, Provincial Administration, Western Cape : an exploratory study - Baardtman, Desmond Andre (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A) -- University of Stellenbosch, 1997.